Second generation of cata-annulated azaacene bisimides: towards rlectron accepting materials [research data] - Hippchen, Nikolai; Heinzel, Elena; Zhang, Cathy K.; Jäger, Patrick; Elter, Maximilian; Ludwig, Philipp; Rominger, Frank; Freudenberg, Jan; Cao, Dennis D.; Bunz, Uwe H. F. (Universität, 2023)
Herein we provide the reserach data for the puplication: "Second Generation of Cata-Annulated Azaacene Bisimides: Towards Electron Accepting Materi...
Gesehen am 04.04.2023
Keywords: Forschungsdaten; Datenbank